Cases and materials on international law - McCorquodale, Robert; Dixon, Martin (Martin J.) (Oxford ; New York : Oxford University Press, 2003)
"International law is now a crucial part of national and international affairs. The fourth edition of Cases & Materials on International Law contains the essential cases and materials that students need in order to understand and analyse the new international legal order. Topics such as the onset of globalization and responses to September 11 shape this new edition. The authors place international law directly in the context of contemporary debates and events. The book's broad coverage, combined with an easy-to-use new text layout, makes it an essential and practical tool for a thorough understanding of this vitally important subject."--BOOK JACKET.
The nature of the international legal system -- The sources of international law -- The law of treaties -- International law and national law -- Personality and recognition -- International human rights law -- Sovereignty over territory -- Jurisdictional sovereignty -- Immunities from national jurisdiction -- Law of the sea -- State responsibility -- International environmental law -- International economic law -- The use of force, collective security and peacekeeping -- Peaceful settlement of international disputes.
Dixon's name appears first on the earlier edition.
Includes bibliographical references (pages xvii-xix) and index.
Keywords: International law -- Cases; Droit international -- Jurisprudence; International law; Trials, litigation, etc